Establishing relational responding in accordance with opposite as generalized operant behavior in young children - Paul M. Smeets (International Journal of Psychology and Psychological Therapy, 2004)
The current study constituted the first attempt to generate repertoires of relationalresponding in accordance with opposite, as generalized operant behavior, whenthey are found to be absent in young children. Three children, aged between 4 and6 years, participated in the study. A basic problem-solving task was adopted fromprevious research to test and train patterns of relational responding in accordancewith opposite. This task involved presenting a child with various numbers ofidentically-sized paper coins and providing the following instructions, for example:This coin buys many (or few) sweets, and is opposite to this coin, which wouldyou take to buy as many sweets as possible? All three participants failed to passbaseline tests for specific patterns of relational responding in accordance with opposite.Various interventions, including training and testing across different stimulus setsand across different numbers of sets, were then successfully used with all participantsto establish these relational responses as well as increasingly complex patterns ofopposite responding. Generalization tests also demonstrated that the relationalresponding generalized to novel stimuli and experimenters. In addition, the use ofa non-contingent reinforcement condition for one participant, during which noimprovement was made, together with contingency reversals for all three participants,indicated that the trained and tested opposite responding may be considered a formof generalized operant behavior. These findings support previous research and lendpositive support to Relational Frame Theorys approach to derived relationalresponding, and to the functional analysis of human language and cognition. Alternativeinterpretations of the data are also considered.